2018
DOI: 10.1016/j.envpol.2018.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxidation of arsenite to arsenate using tunable K+ concentration in the OMS-2 tunnel

Abstract: Cryptomelane-type octahedral molecular sieve manganese oxide (OMS-2) possesses high redox potential and has attracted much interest in its application for oxidation arsenite (As(III)) species of arsenic to arsenate (As(V)) to decrease arsenic toxicity and promote total arsenic removal. However, coexisting ions such as As(V) and phosphate are ubiquitous and readily bond to manganese oxide surface, consequently passivating surface active sites of manganese oxide and reducing As(III) oxidation. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Ferrihydrite and hematite, which showed opposite adsorption affinities to both As(III) and As(V), were used to perform the Donnan experiment. Considering that As(III) oxidation by dissolved oxygen is very slow, the dissolved oxygen in this study was not further removed by introducing an inert gas [4,41]. Arsenic concentration in the ferrihydrite chamber rapidly decreased after addition of As(III), whilst with Mn oxide there was a slight increase (Figure 4a), suggesting that most of the As(III) species may be rapidly adsorbed by ferrihydrite without further diffusion into the Mn oxide chamber.…”
Section: Aqueous Arsenic Dynamics Within Donnan Reactormentioning
confidence: 99%
“…Ferrihydrite and hematite, which showed opposite adsorption affinities to both As(III) and As(V), were used to perform the Donnan experiment. Considering that As(III) oxidation by dissolved oxygen is very slow, the dissolved oxygen in this study was not further removed by introducing an inert gas [4,41]. Arsenic concentration in the ferrihydrite chamber rapidly decreased after addition of As(III), whilst with Mn oxide there was a slight increase (Figure 4a), suggesting that most of the As(III) species may be rapidly adsorbed by ferrihydrite without further diffusion into the Mn oxide chamber.…”
Section: Aqueous Arsenic Dynamics Within Donnan Reactormentioning
confidence: 99%
“…18–20 Luo et al 21 found that K + concentration significantly affected the magnetism of OMS-2. Hou et al enhanced the oxidation of benzene 18 and arsenite 22 by tuning the K + concentration in the OMS-2 tunnel. Moreover, Hamaguchi et al 23 investigated the effect of K + content on the NO-adsorption properties and suggested that the adsorption sites of NO x were the K sites.…”
Section: Introductionmentioning
confidence: 99%
“…This means that manganese oxide only acts as an oxidant for As(III) oxidation, rather than as a catalyst. In addition, a reduction in oxidation activity may occur in the presence of coexisting ions such as phosphate in arsenic‐containing wastewater . This is due to the favorable adsorption of coexisting ions onto manganese oxide surfaces, which then occupy and passivate its surface active sites .…”
Section: Introductionmentioning
confidence: 99%